2013
DOI: 10.1097/ta.0b013e31829617c6
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow mononuclear cells therapy attenuates activated microglial/macrophage response and improves spatial learning after traumatic brain injury

Abstract: Background Autologous bone marrow-derived mononuclear cells (AMNC) have shown therapeutic promise for central nervous system insults such as stroke and traumatic brain injury (TBI). We hypothesized that intravenous injection of AMNC provides neuroprotection which leads to cognitive improvement after TBI. Methods A controlled cortical impact (CCI) rodent traumatic brain injury (TBI) model was used to examine blood-brain barrier permeability (BBB), neuronal and glial apoptosis and cognitive behavior. Two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 29 publications
2
58
0
5
Order By: Relevance
“…MNCs are a heterogeneous population of cells that include mesenchymal stem cells, hematopoietic progenitor cells, endothelial progenitor cells, and several different committed cells of various lineages. Previous reports have demonstrated that MNCs conferred beneficial effects against various types of brain damage, including models of focal cerebral ischemia, transient global cerebral ischemia, chronic cerebral ischemia, and traumatic brain injury [9,[31][32][33]. In this study, we now show that intravenous administration of autologous MNCs reduces injury and enhances recovery in the autologous blood injection ICH model.…”
Section: Discussionsupporting
confidence: 50%
“…MNCs are a heterogeneous population of cells that include mesenchymal stem cells, hematopoietic progenitor cells, endothelial progenitor cells, and several different committed cells of various lineages. Previous reports have demonstrated that MNCs conferred beneficial effects against various types of brain damage, including models of focal cerebral ischemia, transient global cerebral ischemia, chronic cerebral ischemia, and traumatic brain injury [9,[31][32][33]. In this study, we now show that intravenous administration of autologous MNCs reduces injury and enhances recovery in the autologous blood injection ICH model.…”
Section: Discussionsupporting
confidence: 50%
“…These important variables can be concordant but not merged for a meta-analysis. For example Evans Blue dye extravasation can show a 40% reduction in blood-brain barrier permeability with bone marrow derived mononuclear cells (52), and similar results can be obtained using an Alexa-Fluor fluorescent dye with permeability mapping (75). However, accuracy is lost in trying to harmonize the effect magnitude using different measurement techniques.…”
Section: Discussionmentioning
confidence: 69%
“…Additional animal models have shown that administration of bone marrow derived stem cells is able to illicit an increase in the regulatory T cell response following injury (see figure 4) and increase the M2:M1 ratio of macrophages and microglia in the acute phase (Walker et al, 2012a). This alteration has also been shown with BM-MNC and may be due to a proapoptotic CC3 dependent pathway that is selective for the activated microglial population (Bedi et al, 2013b). While attenuation of the inflammatory response occurs acutely, the duration of this change is unknown and other experiments have shown the prolonged M1 response found in TBI to be associated with white matter injury .…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…Finally, preservation or restoration of the blood brain barrier by cell therapies could have beneficial effects on the inflammatory response to injury. Multiple studies in animal models have shown intravenous administration of BM-MNC, MAPC and MSC to preserve blood brain barrier integrity (Bedi et al, 2013b;Menge et al, 2012;Walker et al, 2012a;Walker et al, 2010b). …”
Section: Accepted Manuscriptmentioning
confidence: 99%